Determining Groundwater Potential Using Vertical Electrical Sounding Method In Manggar, Balikpapan City, Indonesia. - Febrian Sastrawan; Rahmania; Meidi Arisalwadi (Journal of Geoscience, Engineering, Environment, and Technology, 2020)
Clean water requirement in Manggar Urban Village of Balikpapan City is rising along with population growth. The main source of clean water that can be used is ground water in the aquifer layer. The Study of groundwater potential was conducted using vertical electrical sounding (VES) method to determine the presence and types of aquifer layers. The measurements along four measurement points revealed four aquifers buried in depth ranging from 48 to 53 m below the surface. The layer which is potential to be an aquifer is a sand layer with moderate-sized grain. The resistivity values for sand layer at each measurement point vary from 221 to 281Ωm. The estimation of sand to be an aquifer layer was supported by the calculation of formation factors. The calculation was based on the ratio of resistivity values from pore-filling water and resistivity values from water-saturated rocks layer. The aquifer revealed in this study is categorized as unconfined aquifer because the upper layer is restricted by sandy clay. The resistivity values vary from 12.8 to 35.4 Ωm which behaved as an aquitard layer. However, low resistivity values between 9.6 to 20 Ωm are detected under the aquifer layer. The layer is identified as clay which behaved as an impermeable layer or aquiclude.